Deciphering Hussein Huzni Mukriani's Historiography: A Critical Examination of “The History of the Soran Princes” - Othman, Hardi Hama Saeed; Abdalla, Shabaz (El Tarikh : Journal of History, Culture and Islamic Civilization, 2024)
This research delves into Hussein Huzni Mukriani's approach to historical writing, specifically examining his book titled "The History of the Soran Princes." The primary objective is to scrutinize Mukriani's methodology in narrating the history of Soran princes and address key research inquiries. How did Mukriani perceive the essence of history? What roles and objectives did history serve, and what sources informed his historical account of the Soran princes? What motivated Mukriani in documenting the history of the Soran princes? Did he adhere to established scientific and historical research methodologies? Our research meticulously follows all stages of scientific inquiry, employing the historical-analytical research method. The key findings include the incorporation of established historical research methods in Mukriani's work and a discernible adherence to the stages of scientific research. The research sheds light on Mukriani's approach to chronicling the history of Soran princes, emphasizing chronological recording and narrative presentation. Mukriani's writing style in this book exhibits distinct characteristics, encompassing information reception, summarization, chronological and narrative structuring, as well as critical evaluation.